Determinants influencing liquidity of pharmaceutical firms listed on the Hanoi Stock Exchange - NGUYEN, VAN HAU; DO, DUC TAI; NGUYEN, THI BICH LIEN; TRAN, THI THU THUY (The journal of contemporary issues in business and government, 2021)
The study investigates factors affect the liquidity of pharmaceutical firms listed on the Hanoi Stock Exchange (HNX). The study employs a set of aggregated data from 10 pharmaceutical firms listed on the HNX. The research uses both qualitative and quantitative research methods. For the quantitative research method, the supporting tool is Stata13 software. The results show that assets structure (AS) factor and Return on sales (ROS) factor have a positive impact on liquidity with two observed variables, Quick Ratio-QR and Current Ratio-CCR; Return on equity (ROE) factor negatively effects the current ratio (CCR) and quick ratio (QR); Debt ratio (DR) has a negative relationship with current ratio (CCR); the rest of factors do not affect QR, CRR. Based on the findings, some recommendations have been proposed to help the pharmaceutical firms listed on the Hanoi Stock Exchange improving better the liquidity in the future.